2015
DOI: 10.3399/bjgp15x684001
|View full text |Cite
|
Sign up to set email alerts
|

What to give the patient who has everything? A qualitative study of prescribing for multimorbidity in primary care

Abstract: BackgroundUsing clinical guidelines in the management of patients with multimorbidity can lead to the prescription of multiple and sometimes conflicting medications. AimTo explore how GPs make decisions when prescribing for multimorbid patients, with a view to informing intervention design. Design and settingIn-depth qualitative interviews incorporating chart-stimulated recall with purposively sampled GPs in the Republic of Ireland. MethodGrounded theory analysis with iterative theory development. ResultsTwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(182 citation statements)
references
References 44 publications
10
171
0
1
Order By: Relevance
“…The themes were integrated into the clinical vignette survey, and concerned 'patient complexity' and 'treatment goals/strategy', as these concepts were both considered as influencing GPs' management. 12,18,22 Concerning decision support, no a priori themes were defined. After the first meeting, the audio-tape was transcribed verbatim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The themes were integrated into the clinical vignette survey, and concerned 'patient complexity' and 'treatment goals/strategy', as these concepts were both considered as influencing GPs' management. 12,18,22 Concerning decision support, no a priori themes were defined. After the first meeting, the audio-tape was transcribed verbatim.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the methods chosen in previous studies, 11,12,17,18,22,29,30 this study incorporated the assessment of case vignettes based on fictitious patients into focus group sessions, which yielded information about variation in medication adjustments between GPs, as well as considerations for the choices made. This study therefore clearly showed that, for similar patients, GPs executed their medication management strategy quite differently.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…A recent study in Ireland of how general practitioners make compromises when prescribing for patients with multimorbidity is a helpful contribution to knowledge in this regard (Sinnott, Mc Hugh, Boyce and Bradley 2015).…”
Section: Improve the Evidence Base On Medicine Optimisation Interventmentioning
confidence: 99%
“…They describe this decision-making process as 'satisficing', where doctors accept care that is satisfactory and sufficient for particular patients. 12 The study opens the 'black box' on what is going on in the mechanism of prescribing decisions in complex situations, revealing the tacit processes. It is a substantial contribution to the body of evidence that promises to emerge to guide professionals and patients on how best to prescribe in multimorbidity.…”
Section: Why Prescribe In Multimorbidity?mentioning
confidence: 99%
“…Making such tacit ideas explicit is important in developing skills to care for patients with multimorbidity, for the education of professionals caring for them, and to be able to maintain accountability by more accurately documenting the rationale behind decisions made. 11 Sinnott et al's rigorously conducted qualitative study, which appears in this issue, 12 seeks to understand how GPs make prescribing decisions in patients with multimorbidities. They describe this decision-making process as 'satisficing', where doctors accept care that is satisfactory and sufficient for particular patients.…”
Section: Why Prescribe In Multimorbidity?mentioning
confidence: 99%